RIFM fragrance ingredient safety assessment, isophytol, CAS Registry Number 505-32-8. (October 2015) - Api, A.M.; Belsito, D.; Bhatia, S.; Bruze, M.; Calow, P.; Dagli, M.L.; Dekant, W.; Fryer, A.D.; Kromidas, L.; La Cava, S.; Lalko, J.F.; Lapczynski, A.; et al.
Highlights: Isophytol safety assessment based on RIFM's criteria. Safety assessment based on 7 Human health endpoints plus environmental. Repeated dose toxicity was determined to give the most conservative systemic derived NO[A]EL. An acceptable MOE was obtained.